Phylogenetic analyses, morphological characteristics, and host specificity of a smut fungus on Zonotriche (Poaceae) from Tropical Africa reveal a new species, Tilletia zonotriches (Tilletiaceae) - Denchev, Teodor T.; Denchev, Cvetomir M.; Fraiture, André; Kemler, Martin (Phytotaxa, 2026)
Tilletia species are highly specialized parasitic fungi on grasses. During examination of specimens of grasses in herbarium of the Meise Botanic Garden, Belgium, an ovariicolous smut fungus belonging to Tilletia was found on specimens of Zonotriche decora from the D.R. Congo and Zambia. These were the first finds of Tilletia specimens on Zonotriche. To clarify the taxonomic status of this species, we conducted a molecular study based on ITS and LSU rDNA sequences. The phylogenetic analyses indicate that this species differs from the Tilletia species with available molecular data. Additionally, this species possesses a distinctive morphological character, by which it can be easily distinguished from all species currently recognized in Tilletia. It produces by far the largest-sized spores in Tilletia, (45–)48–63(–68) μm long. Based on molecular and morphological evidence, and host specialization, a new species, Tilletia zonotriches, is described and illustrated. The phylogenetic placement and affinities of the new species in Tilletia are analyzed. Tilletia zonotriches differs from the only known smut fungus on Zonotriche, Macalpinomyces zonotriches on Z. inamoena from Zambia, by having significantly larger spores.